HBV‐Induced Increased N6 Methyladenosine Modification of PTEN RNA Affects Innate Immunity and Contributes to HCC. Issue 2 (7th November 2020) - Kim, Geon‐Woo; Imam, Hasan; Khan, Mohsin; Mir, Saiful Anam; Kim, Seong‐Jun; Yoon, Seung Kew; Hur, Wonhee; Siddiqui, Aleem
Abstract : Background and Aims: Epitranscriptomic modification of RNA has emerged as the most prevalent form of regulation of gene expression that affects development, differentiation, metabolism, viral infections, and most notably cancer. We have previously shown that hepatitis B virus (HBV) transcripts are modified by N6 methyladenosine (m 6 A) addition. HBV also affects m 6 A modification of several host RNAs, including phosphatase and tensin homolog (PTEN), a well‐known tumor suppressor. PTEN plays a critical role in antiviral innate immunity and the development of hepatocellular carcinoma (HCC). Reports have shown that PTEN controlled interferon regulatory factor 3 (IRF‐3) nuclear localization by negative phosphorylation of IRF‐3 at Ser97, and PTEN reduced carcinogenesis by inhibiting the phosphatidylinositol‐3‐kinase (PI3K)/AKT pathway. Approach and Results: Here, we show that HBV significantly increases the m 6 A modification of PTEN RNA, which contributes to its instability with a corresponding decrease in PTEN protein levels. This is reversed in cells in which the expression of m 6 A methyltransferases is silenced. PTEN expression directly increases activated IRF‐3 nuclear import and subsequent interferon synthesis. In the absence of PTEN, IRF‐3 dephosphorylation at the Ser97 site is decreased and interferon synthesis is crippled. In chronic HBV patient biopsy samples, m 6 A‐modified PTEN mRNA levels were uniformly up‐regulated with a concomitant decrease of PTEN mRNA levels. HBV gene expression also activated the PI3K/AKT pathway by regulating PTEN mRNA stability in HCC cell lines. Conclusions: The m 6 A epitranscriptomic regulation of PTEN by HBV affects innate immunity by inhibiting IRF‐3 nuclear import and the development of HCC by activating the PI3K/AKT pathway. Our studies collectively provide new insights into the mechanisms of HBV‐directed immune evasion and HBV‐associated hepatocarcinogenesis through m 6 A modification of the host PTEN mRNAs.